Differential Impact of Plasma Homocysteine Levels on the Periventricular and Subcortical White Matter Hyperintensities on the Brain - Lee, Kee Ook; Woo, Min-Hee; Chung, Darda; Choi, Jung-Won; Kim, Nam-Keun; Kim, Ok-Joon; Oh, Seung-Hun (Frontiers in Neurology, 2019)
Background: The clinical significance of cerebral white matter hyperintensities (WMH) on brain magnetic resonance imaging (MRI) has recently increased, and recognized now as a risk factor for future stroke and dementia. High levels of plasma homocysteine (Hcyt) are associated with cerebral WMH. Recent studies suggest a different anatomy and physiology in the arteriolar system may be supplied to the periventricular and deep subcortical white matter. We hypothesize that plasma Hcyt levels have differing impacts on periventricular WMH (PVWMH) than on deep subcortical WMH (DSWMH). Methods: We evaluated plasma Hcyt levels from 937 neurologically healthy participants. The severity of PVWMH and DSWMH was evaluated by the use of a manual grading scale. Moderate to severe PVWMH and DSWMH levels were defined when the Fazekas score was two or three, respectively. Predominant PVWMH (pred-PVWMH) and predominant DSWMH (pred-DSWMH) were defined as having a difference of Fazekas score between PVWMH and DSWMH of two or more. Other confounding variables including age, sex, vascular risk factors, and estimated glomerular filtration rate (eGFR) were also analyzed. Results: Logistic regression revealed that, after adjusting for the confounding variables, PVWMH was associated with old age, hypertension, diabetes mellitus, low eGFR, and high plasma Hcyt levels. DSWMH was associated with old age, hypertension, and hypercholesterolemia but not with plasma Hcyt levels. Plasma Hcyt levels were associated with pred-PVWMH but not with pred-DSWMH. Conclusions: High plasma Hcyt levels are strongly associated with the development of PVWMH but not DSWMH. Our results suggest that different pathogeneses exist for PVWMH and DSWMH and that dysregulated Hcyt metabolism plays a role in the development of PVWMH.